Acute liver failure caused by hepatitis E virus genotype 3 and 4: A systematic review and pooled analysis. (25th May 2018) - Haffar, Samir; Shalimar,; Kaur, Ravinder J.; Wang, Zhen; Prokop, Larry J.; Murad, Mohammad H.; Bazerbachi, Fateh
Abstract: Background & Aims: Acute liver failure caused by hepatitis E virus genotype 3 and 4 has been rarely described. Because of the presence of a short golden therapeutic window in patients with viral acute liver failure from other causes, it is possible that early recognition and treatment might reduce the morbidity and mortality. We performed a systematic review and pooled analysis of acute liver failure caused by hepatitis E virus genotype 3 and 4. Methods: Two reviewers appraised studies after searching multiple databases on June 12th, 2017. Appropriate tests were used to compare hepatitis E virus genotype 3 vs 4, suspected vs confirmed genotypes, hepatitis E virus‐RNA positive vs negative, and to discern important mortality risk factors. Results: We identified 65 patients, with median age 58 years (range: 3‐79), and a male to female ratio of 1.2:1. The median bilirubin, ALT, AST and alkaline phosphatase (expressed by multiplication of the upper limit of normal) levels were 14.8, 45.3, 34.8 and 1.63 respectively. Antihepatitis E virus IgG, antihepatitis E virus IgM and hepatitis E virus‐RNA were positive in 84%, 91% and 86% of patients respectively. The median interval from symptoms onset to acute liver failure was 23 days, and 16 patients underwent liver transplantation. Final outcome was reported in 58 patients and mortality was 46%. Age was a predictor of poor prognosis in multivariate analysis. No important differences were found between patients infected with genotype 3 vs 4, patients with confirmed vs suspected genotypes, or patients with positive vs negative RNA. Conclusion: Acute liver failure caused by hepatitis E virus genotype 3 and 4 is rare, similar between genotypes, occurs commonly in middle‐aged/elderly patients and has a very high mortality. Age is predictive of poor prognosis in multivariate analysis.